Pengaruh Spiritualitas di tempat kerja terhadap Produktivitas Kerja Karyawan yang dimediasi oleh Sikap Kerja Positif di Whiz Prime Hotel Khatib Sulaiman Padang - Yuliandri, Desi; Surenda, Rian (Departemen Pariwisata Universitas Negeri Padang, 2025)
This study aims to examine the effect of workplace spirituality on employee productivity mediatedby positive work attitudes at Whiz Prime Hotel Khatib Sulaiman Padang. A quantitative approachwith a survey method and data analysis using Structural Equation Modeling (SEM) based on Partial Least Square (PLS) was employed. Data were collected from the entire population,142 consisting of 60 hotel employees. The research instrument was a Likert-scale questionnaire. Findings revealed that workplace spirituality, positive work attitude, and employee productivity were all categorized as very good, with mean values of 4.30, 4.32, and 4.31 respectively on a 1–5 scale.The results of hypothesis testing indicate that workplace spirituality has a positive and significant effect on positive work attitude, with a path coefficient of 0.639 (t-statistic = 8.805, pvalue = 0.000). Furthermore, positive work attitude significantly influences employee productivity,with a coefficient of 0.735 (t-statistic = 11.812, p-value = 0.000). Additionally, workplace spirituality indirectly affects employee productivity through positive work attitude, with a mediated path coefficient of 0.469 (t-statistic = 5.854, p-value = 0.000). These findings suggest that enhancing workplace spirituality and fostering positive work attitudes can substantially improve employee productivity, offering valuable insights for human resource management in the hospitality industry.